The Effect of Transformational Leadership and Work Motivation on Teacher Performance at Vocational High School Bina Mandiri Cileungsi - HM Usman; Rofiq Noorman Haryadi (Sharia Business Management Department of STEBIS Bina Mandiri, 2023)
using the slovin formula, then the data collection technique used simple random sampling technique which is part of the probability sampling technique. The data collection method is carried out through primary data collection in the form of observation and questionnaires. Secondary data through literature study. Instrument testing is carried out through validity and reliability tests, classical assumption tests are carried out through normality tests, heteroscedasticity tests, autocorrelation tests and multicollinearity tests. The data analysis technique uses the frequency distribution of quantitative data, multiple linear regression analysis, correlation coefficient, determination coefficient, T test and F test. The results of the research based on the processing of the F test can be concluded that the value of F is 14.805 > 5.23, so Ho is rejected and Ha is accepted. With these results transformational leadership variables (X1) and motivation (X2) both have an effect on performance (Y).